Medidas da concentração de Radônio-222 em água de poço e solo da região do Pinheirinho em Curitiba e proposta de mitigação da água - Mafra, Karina Cristina (2011)
More than 50% of the effective annual radiation dose received by a human being is related to the Radon and its progeny. Among main mechanisms that bring Radon inside the dwelling are the soil emanation and radon release from the water. This present work represents a proposal of mitigation, method to reduce Radon-222 levels in well water, using the process of water aeration and measurements of Radon-222 in the water and soil. Samples were collected in a pit and soil in the region of "Pinheirinho" in the city of "Curitiba" Brazil. The Measurements were taken during the period of February till June of 2011, being analyzed by an average of ten samples of each water collected, among them eight were under the process of aeration. The measurements were obtained with ionization chamber Randon Professional Monitor (AlfaGUARD), a device that checks concentrations of Radon in the range of 2-2x106 Bq/L, adjusted in a flow of 0.5L/min, with approximate time of 60 minutes, in the laboratory for Ionizing Radiation of the Univeristy " Federal do Parana" (UTFPR). The levels of concentration of Radon-222 were measured by the software called AlfaEXPERT, and suitable formulations characterized the concentration of this gas in the water by correcting the time decay due to the delay in the collection of samples for measurements. The method of mitigation used was aeration, called Diffusing Aeration, in which there is the gasification of water in a process that injects air by an aerator connected in a porous plate during a period of 24 hours in 4 days, since the half life of Radon is approximately 3,82 days, for the reduction of the concentration of Radon-222 on samples. Initially samples had concentrations of Radon-222 aproximately from 20 Bq/L, a level above 11.11 Bq/L recomended by USEPA (United States Enviromental Protection Agency). After Applying the measurements to mitigate these samples of water, the concentration of Radono-222 decreased satisfactorily and remained below the expected value by the natural decaying of the water.